PENDIDIKAN AGAMA ISLAM SEBAGAI PILAR PENGUATAN MORAL PESERTA DIDIK DI TENGAH GLOBALISASI - Muna Hatijah; Ratna Rahim; Hasnahwati (Jurnal Andi Djemma/Jurnal Pendidikan, 2026)
This research aims to examine the role of Islamic Religious Education in strengthening morals amidst the phenomenon of globalization with its very rapid development. Globalization has a real impact on many aspects of life, including moral, social and cultural values. In these conditions, Islamic Religious Education functions as an important pillar to shape the morals and morals of the younger generation, by instilling moral and spiritual values that are in line with Islamic teachings. This research uses a qualitative approach with literature study methods, as well as analysis of various relevant sources, including books, articles and previous research. The research results show that Islamic Religious Education has a very important role in providing a strong moral foundation for individuals to face the challenges posed by globalization, such as changes in social values, unfiltered information flows, and the influence of foreign cultures. Islamic religious education, which focuses on the formation of noble morals, honesty, responsibility and social care, can shape the character of students who are able to adapt to global dynamics without losing their moral and religious identity. Therefore, Islamic Religious Education needs to be optimized through a holistic and integrative approach, involving the active role of teachers, parents and the community. Thus, Islamic Religious Education can be the main pillar in building an ethical, moral and civilized society in the midst of globalization.